Structural, Optical Properties and Raman Spectroscopy of In2O3 Doped LiTaO3 Thin Films - Nani Djohan; Budi Harsono; Johansah Liman; Hendradi Hardhienata; Irzaman (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
In this experiment, undoped, 2 wt.%, 4 wt.% and 6 wt.% In2O3 doped LiTaO3 thin films were successfully prepared by utilizing a spin coater to carry out chemical solution deposition on the substrate surface (CSD method). The films were grown on the p-type Si (100) substrates with 2 M in 2-methoxyethanol precursor, whose solubility was twisted at 4000 rpm for 30 seconds. Crystalline formation of the films was carried out at annealing temperature 850 oC, held for 15 hours at a temperature rise rate of 1.67 oC/min. In term of XRD analysis, the structural properties of LiTaO3 thin film undergo increment in crystallite size and lattice parameter values as the concentration of indium doping increase. The optical properties and Raman spectra of the films were then obtained using UV-Vis spectrometer and Raman spectroscopy. From the XRD measurement, the result shows a hexagonal crystal structure with lattice parameters a = 5.032-5.051 Å and c = 13.643-13.676 Å, and from the UV-Vis data, we observed that the films have a 5.034-5.184 Ev energy gap with 1.70364373 – 1.70364377 refractive index. Raman analysis produces peaks of LiTaO3, A1TO10 (In2O3) and A1LO10 (In2O3). Based on the characterization results, it can be concluded that the 6 wt% In2O3 doped LiTaO3 thin films are very promising for application as a light sensor.